Comparative Cost of Virtual Reality Training and Live Exercises for Training Hospital Workers for Evacuation. Issue 9 (September 2019) - Farra, Sharon L.; Gneuhs, Matthew; Hodgson, Eric; Kawosa, Burhan; Miller, Elaine T.; Simon, Ashley; Timm, Nathan; Hausfeld, Jackie
Abstract : Adoption of virtual reality technology may be delayed due to high up-front costs with unknown returns on that investment. In this article, we present a cost analysis of using virtual reality as a training tool. Virtual reality was used to train neonatal intensive care workers in hospital evacuation. A live disaster exercise with mannequins was also conducted that approximated the virtual experience. Comparative costs are presented for the planning, development, and implementation of both interventions. Initially, virtual reality is more expensive, with a cost of $229.79 per participant (total cost $18 617.54 per exercise) for the live drill versus $327.78 (total cost $106 951.14) for virtual reality. When development costs are extrapolated to repeated training over 3 years, however, the virtual exercise becomes less expensive with a cost of $115.43 per participant, while the cost of live exercises remains fixed. The larger initial investment in virtual reality can be spread across a large number of trainees and a longer time period with little additional cost, while each live drill requires additional costs that scale with the number of participants.